Assessing the Efficiency and Results of Implementing Programs: Theory, Methodology and Practice (illustrated by the Republic of Kalmykia) - O. V. Maksimchuk; S. B. Boldyreva (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Research topicality is stipulated by system contradictions at the current stage of global economy development, which creates challenges and acute agenda for national economy of the Russian Federation and economy of its entities that face objectives of reaching target figures of social and economic development in view of strategic landmarks and priorities of development based on state programs up to 2030. The goal of the article is to analyze effectiveness of state regulators of cutting the gap and disproportions in the development of Russian regions based on sampling data concerning state program resection, including materials dealing with the Republic of Kalmykia. Attaining of the set goal is ensured by resolving the following problems: to identify theoretical approach to understanding state programs as a tool of managing impacts of different factors, brief review and analysis of methodology and methods of estimating efficiency and results of implementing state programs; to find problem zones in stated methodology and methods and to formulate proposals aimed at their alteration and upgrading. The research findings can be important for further investigation and practical use by responsible executors at departmental bodies for collecting and processing information dealing with state program implementation.